Chronic Energy Deficiency and Its Associated Factors among Pregnant Women Living in Rural Areas, Indonesia: A Community Based Study - Anggriani Harahap, Dewi; Afrinis, Nur; Lasepa, Wanda; Apriyanti, Fitri (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Chronic energy deficiency (CED) in Indonesia is highly prevalent among pregnant women, becoming a public health problem that requires immediate action due to the adverse effects on the growth and development of the fetus as well as the health of the mother. This study aims to assess factors associated with CED among pregnant women in a particular rural area, in Siak Regency, which has a high prevalence of CED. A cross-sectional study was employed involving 122 pregnant women in the first and second trimesters from December 2024 to January 2025. Probability proportional to size (PPS) was used to select the subjects in 10 villages. Mid-Upper Arm Circumference (MUAC) was measured to determine CED incidence with less than 23.5 cm as a cut-off point. A structured questionnaire was used to collect socio-demographic, food security, and food taboo data. The HFIAS questionnaire was used to collect food security data. This study has found that the prevalence of CED among pregnant women is 35.2%. In bivariate analysis, economic status, dietary diversity, parity, dietary pattern, food security, and food taboo have a significant association with CED. After adjusted by several variables using binary logistic, parity (AOR: 25.47; 95% CI:2.6- 78.23), food security (AOR: 6.19; 95% CI: 2.05- 18.73) and food taboo (AOR: 6.44; 95%CI: 2.0- 20.648) are exhibited to be determinant factors of CED with p-value less than0.05. The percentage of CED among pregnant women is higher compared to the national prevalence, which leads to urgent actions. Interventions targeting the causes of CED, such as parity, food security, and food taboo, are essential to reduce the incidence of CED. The results of this study are expected to guide policymakers in creating innovative interventions to reduce CED among pregnant women.